English Writing Experiences Assisted by Grammarly and Teacher Feedback to Learners with Different Learning Styles (Papeles, 2026)
Introduction: Writing in English has challenges for learners of a foreign language, such as grammar, cohesion, coherence, and sentence structure. Integrating learning styles and personalized feedback into language instruction can benefit writing skills. Additionally, Grammarly offers feedback that may complement teacher feedback in English instruction. Methodology: This qualitative case study was carried out with a sample consists of ten voluntary EFL high school learners: seven males and three females; aged 16-17, and A2 proficiency. Participants practiced English writing in the summer of 2025 for 33 days. Results and discussions: The results showed that the most common learning style was individual (n=4). They wrote mainly at night. They reported positive emotions (comfort, excitement) and negative emotions (nervousness, confusion) toward Grammarly Feedback, whereas for teacher feedback only positive emotions. Participants (n=6) preferred more teacher over Grammarly feedback regarding their learning styles; they particularly valued oral explanations. Both types of feedback helped them improve their texts. The preference for teacher feedback may reflect the need for explicit explanations required in auditory learning style. Grammarly demonstrated its utility as a learning tool, but inadequate to be used alone at this proficiency level. Conclusions: Learners treated AI feedback as a learning tool while maintaining authorship of their writing. Combining Grammarly with teacher oral and written feedback is recommended for beginner EFL writers. Lastly, it is important to consider learners' affective responses when using AI feedback in foreign language instruction.